Application of Liquid Organic Fertilizer Derived from Vegetable Waste and NPK on Sweet Corn Plants (Zea mays saccharata Sturt) - Maria Lusia; Erni Hawayanti; Neni Marlina; Dali Dali; Bernard Juliantara (Journal of Global Sustainable Agriculture, 2024)
Corn is an alternative crop that replaces staple foods other than rice.  Efforts to increase corn production in less fertile land with the application of liquid organic fertilizer (POC) vegetable waste and NPK provide nutrients and improve soil structure so that roots develop well. This study aims to obtain the right POC and NPK dose to increase the growth and production of sweet corn. The method used is field experiments.  The layout on the field uses a Split Plot Design with 12 combinations repeated 3 times.  The size of the plot is 2 x 2 m.  As the main plot, namely NPK fertilizer K1 (30 g/plot), K2 (60 g/plot), and K3 (90 g/plot).  As a subplot, namely POC of vegetable waste P0 (0 ml/L), P1 (10 ml/L) P2 (20 ml/L), and P3 (30 ml/L). The application of POC 30 ml/L with NPK fertilizer 30 g/plot is the best combination of treatment in increasing production by 12.6 kg/plot or 25.20 tons/ha.